Mindfulness for smoking cessation (protocol) - Jackson, S; Brown, J; West, R; Norris, E; Livingstone-Banks, J; Lindson, N (Wiley, 2020)
Objectives This is a protocol for a Cochrane Review (intervention). The objectives are as follows: